Opioid use in medical cannabis authorization adult patients from 2013 to 2018: Alberta, Canada - Cerina Lee; Mu Lin; Karen J. B. Martins; Jason R. B. Dyck; Scott Klarenbach; Lawrence Richer; Ed Jess; John G. Hanlon; Elaine Hyshka; Dean T. Eurich (BMC, 2021)
Abstract Background The opioid overdose epidemic in Canada and the United States has become a public health crisis - with exponential increases in opioid-related morbidity and mortality. Recently, there has been an increasing body of evidence focusing on the opioid-sparing effects of medical cannabis use (reduction of opioid use and reliance), and medical cannabis as a potential alternative treatment for chronic pain. The objective of this study is to assess the effect of medical cannabis authorization on opioid use (oral morphine equivalent; OME) between 2013 and 2018 in Alberta, Canada. Methods All adult patients defined as chronic opioid users who were authorized medical cannabis by their health care provider in Alberta, Canada from 2013 to 2018 were propensity score matched to non-authorized chronic opioid using controls. A total of 5373 medical cannabis patients were matched to controls, who were all chronic opioid users. The change in the weekly average OME of opioid drugs for medical cannabis patients relative to controls was measured. Interrupted time series (ITS) analyses was used to assess the trend change in OME during the 26 weeks (6 months) before and 52 weeks (1 year) after the authorization of medical cannabis among adult chronic opioid users. Results Average age was 52 years and 54% were female. Patients on low dose opioids (< 50 OME) had an increase in their weekly OME per week (absolute increase of 112.1 OME, 95% CI: 104.1 to 120.3); whereas higher dose users (OME > 100), showed a significant decrease over 6 months (− 435.5, 95% CI: − 596.8 to − 274.2) compared to controls. Conclusions This short-term study found that medical cannabis authorization showed intermediate effects on opioid use, which was dependent on initial opioid use. Greater observations of changes in OME appear to be in those patients who were on a high dosage of opioids (OME > 100); however, continued surveillance of patients utilizing both opioids and medical cannabis is warranted by clinicians to understand the long-term potential benefits and any harms of ongoing use.